Pesan Hikmah dalam Ajaran Aqiqah Bernuansa Gender: Studi Tematik Hadis-hadis Aqiqah - Zaeni Muhab (UIN Sunan Gunung Djati Bandung, 2023)
Before Islam entered Arab society, they had done the slaughtering of goats or sheep for the birth of a son. The slaughter of these animals is called aqiqah. Arab society does it as a sign of gratitude and happiness for the birth of a son. The purpose of this study was to find out the message of wisdom in the teachings of aqiqah with gender nuances in the thematic study of aqiqah traditions and to find out the teachings of aqiqah with gender nuances in the study of aqiqah traditions. This research is a type of qualitative research with descriptive analysis method and thematic method. This research uses a qualitative approach, where an understanding and research is based on a methodology that studies a social problem and a human problem. The results of this study indicate that aqiqah as a means (wasilah) to ask Allah SWT, to always protect and care for the baby from the temptations of the cursed devil, as well as a sign of gratitude for the blessings of Allah SWT for the birth of a child with aqiqah. The conclusion of this study is that the message of wisdom contained in the teachings of aqiqah is seen based on the nuances of gender, influenced by the social conditions of the Arabs and their ancient thought structures. Where the presence of boys they expect more than girls. In other words, their happiness when they got a boy was more than that of getting a girl. This results in more aqiqah for boys than for girls.